Cognitive Performance, Aerobic Fitness, Motor Proficiency, and Brain Function Among Children Newly Diagnosed With Craniopharyngioma. (3rd May 2019) - Conklin, Heather M.; Ness, Kirsten K.; Ashford, Jason M.; Scoggins, Matthew A.; Ogg, Robert J.; Han, Yuanyuan; Li, Yimei; Bradley, Julie A.; Boop, Frederick A.; Merchant, Thomas E.
Abstract: Objectives: Craniopharyngioma survivors experience cognitive deficits that negatively impact quality of life. Aerobic fitness is associated with cognitive benefits in typically developing children and physical exercise promotes recovery following brain injury. Accordingly, we investigated cognitive and neural correlates of aerobic fitness in a sample of craniopharyngioma patients.Methods: Patients treated for craniopharyngioma [ N =104, 10.0±4.6 years, 48% male] participated in fitness, cognitive and fMRI ( n =51) assessments following surgery but before proton radiation therapy.Results: Patients demonstrated impaired aerobic fitness [peak oxygen uptake (PKVO2 )=23.9±7.1, 41% impaired (i.e., 1.5 SD <normative mean)], motor proficiency [Bruininks-Oseretsky (BOT2)=38.6±9.0, 28% impaired], and executive functions (e.g., WISC-IV Working Memory Index (WMI)=96.0±15.3, 11% impaired). PKVO2 correlated with better executive functions (e.g., WISC-IV WMI r =.27, p =.02) and academic performance (WJ-III Calculation r =.24, p =.04). BOT2 correlated with better attention (e.g., CPT-II omissions r =.26, p =.04) and executive functions (e.g., WISC-IV WMI r =.32, p =.01). Areas of robust neural activation during an n-back task included superior parietal lobule, dorsolateral prefrontal cortex, and middle and superior frontal gyri ( p <.05, corrected). Higher network activation was associated with better working memory task performance and better BOT2 ( p <.001).Conclusions: Before adjuvant therapy, children with craniopharyngioma demonstrate significantly reduced aerobic fitness, motor proficiency, and working memory. Better aerobic fitness and motor proficiency are associated with better attention and executive functions, as well as greater activation of a well-established working memory network. These findings may help explain differential risk/resiliency with respect to acute cognitive changes that may portend cognitive late effects. ( JINS, 2019, 25, 413–425)